Photophysical, optical, and photocatalytic hydrogen production properties of layered-type BaNb2-xTaxP2O11 (x = 0, 0.5, 1.0, 1.5, and 2.0) compounds - Kang, Min Je; Han, Gill Sang; Cho, In Sun (Journal of Materials Science and Technology, 2022)
Layered-type metal phosphates of BaNb2-xTaxP2O11 (x = 0, 0.5, 1.0, 1.5, and 2.0) were synthesized using a solid-state reaction method. The photophysical, optical, and photocatalytic hydrogen production properties of the resulting powders were investigated for the first time. Phase-pure and homogeneous powders with irregular morphologies were obtained at a calcination temperature of 1200 °C. As the Ta content increased, the interlayer distance along the c-axis increased by up to 0.14%. Additionally, the optical bandgap values increased from 3.32 to 3.59 eV. The energy band positions were estimated from the Mott–Schottky measurements. BaNb2P2O11 (x = 0) exhibited the lowest conduction band edge position (−0.14 V vs. the normal hydrogen electrode, NHE), which is located above the water reduction potential (0.0 V vs. NHE). In comparison, BaTa2P2O11 (x = 2.0) exhibited the highest conduction band edge position (−0.29 V vs. NHE), comparable to that of TiO2. The photocatalytic activity for hydrogen produced from splitting water was measured under ultraviolet light irradiation. Notably, BaTa2P2O11 exhibited the highest activity (7.3 μmol/h), which was 15 and 10 times larger than BaNb2P2O11 (0.5 μmol/h) and nano-TiO2 (0.7 μmol/h), respectively. The activity of BaTa2P2O11 increased to 24.4 μmol/h after deposition of the NiOx co-catalyst (1 wt.%), which remained stable during continuous operation (~35 h).
Keywords: Calcination temperature; Conduction band edge; Continuous operation; Irregular morphology; Normal hydrogen electrodes; Photocatalytic hydrogen production; Solid state reaction method; Ultraviolet light irradiation; BaNb2P2O11; Band edge positions; Bandgap; BaTa2P2O11; Layered crystal structure; Photocatalytic hydrogen production